STOCK MARKET REACTIONS ON EXCHANGE RATE VOLATILITY: AN INDIAN EXPERIENCE - Rose, Lyn; Jose, Nithin (International Journal of Research -GRANTHAALAYAH, 2020)
This paper looks at the relationship between Nifty returns and US Dollar - Indian Rupee Exchange Rates. The study looks into the causal relationship between Nifty returns and exchange rate using Granger Causality test. It took daily data covering the period from January, 2009 to June, 2019. In this study, it was found that both variables were non–normally distributed. With the help of Unit Root Test, it was also verified that Nifty returns as well as Exchange rate, were stationary at the first difference form. Using Granger Causality test it is proved there was a bidirectional relationship between Nifty returns and Exchange rates. From the further investigation it is evident there is a causality running from exchange rate return to stock market return. Finally, employing impulse response function it found that there is a negative relationship among the variables.